Turban and black identity: discursive semiotics applied to a Facebook post (Revista de Ensino em Artes, Moda e Design, 2021)
This paper aimed to understand the participation of clothing in the construction of black/African identity in contemporary times. For that, we used discursive semiotics, which was applied to a Facebook post of a black woman, in which she wore the turban and talked about it. The analysis carried out allowed us to understand that the use of the turban implies an identity issue, in which the construction of the black/African identity occurs in opposition to the white/European identity, and occurs within a narrative in which, in the present, there is performative repetition of a clothing practice considered originated by African ancestry. The use of the turban appears, in the post, as a way of granting a euphoric appreciation to the black / African identity. In general, the discourse builds a theme of liberation, since the use of the turban as something euphoric manifests itself as a way to break free from the standard of beauty and the Eurocentric worldview that builds the turban as a symbol of the other and manipulates black people and black women to eradicate it from everyday use in favor of an attempt to come into conjunction with white/European otherness.
Keywords: Turban; Black identity; Discursive semiotics